205k views
4 votes
Can someone help me solve this step by step please. Thanks if u do

Can someone help me solve this step by step please. Thanks if u do-example-1
User KJSR
by
5.7k points

2 Answers

3 votes

3x + 2y = -26 turns into


y =
(-3x)/(2) - 13


2x - 6y = -10 turns into


y =
(1x)/(3) +
(5)/(3)


and you would put that into the solution.


I hope this helped!

User PaulAdamDavis
by
6.5k points
3 votes
3x+2y= -26/×3
2x-6y= -10

9x+6y= -78 (I)
2x-6y=-10 (II)

I+II => 11x= -88
x= -88/11
x= -8

2x-6y= -10
2×(-8) -6y= -10
-16 -6y= -10
-6y= -10+16
-6y= 6
y= 6/-6
y= -1

If you have any questions feel free to ask!I hope I helped :)
User Jaye Renzo Montejo
by
5.9k points